The 100-year-old man who climbed out the window and disappeared - Jonasson, Jonas, 1961-; Bradbury, Rod. (New York : Hyperion, 2012)
Confined to a nursing home and about to turn 100, Allan Karlsson, who has a larger-than-life back story as an explosives expert, climbs out of the window in his slippers and embarks on an unforgettable adventure involving thugs, a murderous elephant and a very friendly hot dog stand operator.
Keywords: Older people -- Fiction